2015
DOI: 10.1177/0284185115580840
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of postcontrast myocardial T1 value and delayed enhancement to reduced cardiac function and serious arrhythmia in dilated cardiomyopathy with left ventricular ejection fraction less than 35%

Abstract: In DCM patients with LVEF <35%, the postcontrast myocardial T1 value correlated with the severity of cardiac dysfunction, and the absence of DE indicated the low risk of SVT. Both MRI parameters should be estimated because they may reflect discrete forms of myocardial damages in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…The majority of studies evaluated the presence or absence of LGE by visual analysis. 4,6,7,10,[13][14][15][16][17][18][19][20]22,[24][25][26][27][28][29]30,32 Duration of follow-up ranged from 1 year to 5.3 years; mean follow up was 3 years. The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The majority of studies evaluated the presence or absence of LGE by visual analysis. 4,6,7,10,[13][14][15][16][17][18][19][20]22,[24][25][26][27][28][29]30,32 Duration of follow-up ranged from 1 year to 5.3 years; mean follow up was 3 years. The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Therefore, further study on the internal mechanism of HF pathology and explore the effective means to block the mechanism, will provide valuable basic research information for clinical treatment of HF. Indeed, certain mutations often induce HF with cardiac arrhythmia that is considered as the potential trigger of sudden cardiac death 62 63 . Thus, both the effective prognostic determination and appropriate cardiac care depend on accurate molecular and genetic diagnoses and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10). More importantly, the occurrence and extent of LGE have been associated with a worse clinical outcome, in particular with impaired ventricular filling and systolic function [83][84][85] and with life-threatening arrhythmias [86][87][88]. A recent study found that galectin-3 predicted the presence and extent of replacement fibrosis at cardiac CMR in a cohort of patients with DCM [89], consistently with the causal role of galectin-3 in the determination of myocardial fibrosis and remodelling.…”
Section: Late Gadolinium Enhancementmentioning
confidence: 94%